Semi-aromatic polyamide film
A semi-aromatic polyamide film with controlled heat shrinkage stress addresses uniform shrinkability issues, ensuring heat resistance and tension application without defects, suitable for wearable devices and voice transmitters.
Patent Information
- Application Number
- JP2023105600
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-06-28
- Publication Date
- 2025-01-17
AI Technical Summary
Existing semi-aromatic polyamide films lack uniform heat shrinkability, leading to issues such as bending, wrinkling, and poor appearance, which are critical for applications in wearable devices and voice transmitters that require heat resistance and tension application.
A semi-aromatic polyamide film with specific heat shrinkage stress ranges (0.2-2.0 MPa at 200°C and 0.5-3.0 MPa at 250°C) and controlled stress differences (≤1.0 MPa) is developed, ensuring uniform shrinkage and tension application without defects.
The film provides heat resistance, prevents bending and wrinkling, and maintains device performance under high heat, offering waterproof and dustproof functions for tactile switches and voice transmitters.
Smart Images

Figure 2025005465000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a semi-aromatic polyamide film having a specific heat shrinkage stress. [Background technology]
[0002] In recent years, wearable devices, healthcare devices, and other electronic devices that are worn on the body have become smaller and more functional. Because such devices are exposed to sweat, rain, and dust, each component is required to have waterproof and dustproof functions. For example, Patent Document 1 discloses the use of a film as a flexible substrate for the operating (functional) part of a tactile switch. The manufacture of the above-mentioned tactile switches and other such products may involve a solder reflow process, so the films used are required to have heat resistance of around 250°C and, at the same time, to have heat shrinkability that prevents bending or wrinkling after heating.
[0003] Furthermore, in a voice transmitter equipped with a membrane member capable of propagating sound from one side to the other and transmitting sound spoken by the wearer to the outside, Patent Document 2 discloses a voice transmitter in which a membrane member made of a heat-shrinkable material is heated and shrunk while held by a holding member, so that the membrane member is held by the holding member with tension applied over almost the entire surface. Voice transmitters, particularly when mounted on masks used in firefighting activities, are required to have particularly high heat resistance, and are required to not significantly impair the device's performance even when exposed to high heat.
[0004] Patent Document 3 discloses a film made of a heat-resistant semi-aromatic polyamide, but the film does not have heat shrinkability suitable for the above-mentioned applications. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2020-147696 A [Patent Document 2] JP 2014-176634 A [Patent Document 3] International Publication No. 2019-031428 Summary of the Invention [Problem to be solved by the invention]
[0006] An object of the present invention is to provide a film which can be uniformly shrunk in its plane when heated, can be given an appropriate tension, and has a good appearance without defects such as warping or wrinkling. [Means for solving the problem]
[0007] As a result of extensive investigations, the present inventors have found that a semi-aromatic polyamide film having a specific heat shrinkage stress can solve the above problems, and have arrived at the present invention. That is, the gist of the present invention is as follows.
[0008] (1) A film made of a semi-aromatic polyamide resin, Thermal shrinkage stress (HS) at 200°C in machine direction (MD) and cross direction (TD) 200,MD , H.S. 200,TD ) are 0.2 to 2.0 MPa, Thermal shrinkage stress (HS) at 250°C in machine direction (MD) and cross direction (TD) 250,MD , H.S. 250,TD ) are each 0.5 to 3.0 MPa. (2)|HS 200,MD -HS 200,TD | and |HS 250,MD -HS 250,TD | is 1.0 MPa or less. (3)||HS 200,MD -HS 200,TD |-|HS 250,MD -HS 250,TDThe semi-aromatic polyamide film according to (1) or (2), wherein || is 0.5 MPa or less. (4) A device comprising the semi-aromatic polyamide film described in (1) above and a film holding part. (5) The device according to (4), wherein the semi-aromatic polyamide film held in the holding portion is thermally shrunk. (6) The device according to (4) or (5), wherein the device is a tactile switch. (7) The device according to (4) or (5), characterized in that the device is a voice transmitter. Effect of the Invention
[0009] When used in a tactile switch, the thermoplastic polyamide film of the present invention can impart waterproof and dustproof functions to each component. The film has heat resistance in the reflow process during manufacturing, and has heat shrinkability that prevents bending or wrinkling after heating. In addition, the thermoplastic polyamide film of the present invention can be used as a membrane component in a voice transmitter, and by heating and shrinking it, it can be held by a holding member with tension applied over almost the entire surface, and even when exposed to high heat, the device performance is not degraded. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] (Semi-aromatic polyamide resin) The semi-aromatic polyamide resin constituting the film of the present invention is obtained by polycondensation of an aromatic dicarboxylic acid component and an aliphatic diamine component.
[0011] Examples of aromatic dicarboxylic acids include terephthalic acid, isophthalic acid, phthalic acid, and naphthalenedicarboxylic acid. The aromatic dicarboxylic acid component preferably contains 60 to 100 mol % of terephthalic acid, more preferably 70 to 100 mol %, and even more preferably 80 to 100 mol %. If the content of terephthalic acid is less than 60 mol %, the heat resistance and low water absorbency of the resulting film may decrease.
[0012] The aliphatic diamine component preferably contains an aliphatic diamine having 6 to 12 carbon atoms as a main component, more preferably contains an aliphatic diamine having 9 to 12 carbon atoms as a main component, and even more preferably contains an aliphatic diamine having 9 or 10 carbon atoms as a main component.
[0013] Examples of the aliphatic diamine having 6 to 12 carbon atoms include linear aliphatic diamines such as 1,6-hexanediamine, 1,7-heptanediamine, 1,8-octanediamine, 1,9-nonanediamine, 1,10-decanediamine, 1,11-undecanediamine, and 1,12-dodecanediamine, and branched aliphatic diamines such as 2-methyl-1,8-octanediamine, 4-methyl-1,8-octanediamine, 5-methyl-1,9-nonanediamine, 2,2,4- / 2,4,4-trimethyl-1,6-hexanediamine, 2-methyl-1,5-pentanediamine, 2-methyl-1,6-hexanediamine, and 2-methyl-1,7-heptanediamine.
[0014] The content of the aliphatic diamine having 6 to 12 carbon atoms in the aliphatic diamine component is preferably 60 mol% or more, more preferably 75 mol% or more, and even more preferably 90 mol% or more. When the content of the aliphatic diamine having 6 to 12 carbon atoms is 60 mol% or more, the obtained film can have both heat resistance and productivity. The aliphatic diamine having 6 to 12 carbon atoms may be used alone or in combination of two or more. When two or more types are used in combination, the content is the total of the two or more.
[0015] The aliphatic diamine component preferably contains 60 to 100 mol %, more preferably 75 to 100 mol %, and even more preferably 90 to 100 mol % of an aliphatic alkylenediamine having 9 carbon atoms. If the content of the aliphatic alkylenediamine having 9 carbon atoms is less than 60 mol %, the heat resistance, low water absorbency, and chemical resistance of the resulting film may be reduced. Examples of the aliphatic alkylenediamine having 9 carbon atoms include linear 1,9-nonanediamine, branched 2-methyl-1,8-octanediamine, 4-methyl-1,8-octanediamine, etc., as described above, and one or more of these can be used. In the present invention, the aliphatic diamine component preferably contains 1,9-nonanediamine and, if necessary, 2-methyl-1,8-octanediamine in a total amount of 60 to 100 mol%, and the molar ratio of 1,9-nonanediamine to 2-methyl-1,8-octanediamine (1,9-nonanediamine / 2-methyl-1,8-octanediamine) is preferably 50 / 50 to 100 / 0, more preferably 70 / 30 to 100 / 0, and even more preferably 75 / 25 to 95 / 5. By using 1,9-nonanediamine and 2-methyl-1,8-octanediamine in the above molar ratio, a film with particularly excellent heat resistance and low water absorption can be obtained.
[0016] An example of such a commercially available semi-aromatic polyamide is Genestar (trade name) manufactured by Kuraray Co., Ltd.
[0017] Examples of the aliphatic diamine other than the aliphatic diamine having 6 to 12 carbon atoms include linear aliphatic diamines such as 1,4-butanediamine and 1,5-pentanediamine.
[0018] The semi-aromatic polyamide may contain a diamine component other than the aliphatic diamine component as the diamine component, within a range that does not impair the effects of the present invention. Examples of the other diamine components include alicyclic diamines such as isophorone diamine, norbornane dimethylamine, and tricyclodecane dimethylamine, and aromatic diamines such as metaxylylene diamine, paraxylylene diamine, metaphenylene diamine, and paraphenylene diamine.
[0019] Within the scope of the present invention, the semi-aromatic polyamide may be used in combination with polyamide raw materials other than those mentioned above. Examples of polyamide raw materials that may be used in combination include lactams such as ε-caprolactam, ζ-enantholactam, η-capryllactam, and ω-laurolactam; and aliphatic dicarboxylic acids such as oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, sebacic acid, dodecanedioic acid, tetradecanedioic acid, and octadecanedioic acid.
[0020] As a guideline for selecting the polyamide raw material and composition, it is preferable to select the melting point of the resulting semi-aromatic polyamide in the range of about 270 to 350° C. If the melting point of the semi-aromatic polyamide is less than 270° C., the heat resistance is insufficient, and if it exceeds 350° C., the processing temperature becomes high and thermal decomposition may occur.
[0021] The semi-aromatic polyamide in the present invention preferably has an intrinsic viscosity [η] of 0.8 to 2.0 dl / g, more preferably 0.9 to 1.8 dl / g, measured in concentrated sulfuric acid at 30° C. When the semi-aromatic polyamide has an intrinsic viscosity [η] within the above range, it is possible to obtain a film that is excellent in formability into a film and excellent in mechanical properties, heat resistance, etc.
[0022] In the present invention, the semi-aromatic polyamide has preferably 10 mol % or more of the terminal groups of the molecular chain blocked with a terminal blocking agent, more preferably a terminal blocking rate of 40 mol % or more, and even more preferably a terminal blocking rate of 70 mol % or more. If the terminal blocking rate is 10 mol % or more, the semi-aromatic polyamide has a small viscosity change during melt molding, and the obtained semi-aromatic polyamide film has excellent physical properties such as appearance and hot water resistance. The end-capping agent is not particularly limited as long as it is a monofunctional compound reactive with the amino group or carboxyl group at the polyamide end, and examples thereof include monocarboxylic acid, monoamine, acid anhydride such as phthalic anhydride, monoisocyanate, monoacid halide, monoester, monoalcohol, etc. Among them, monocarboxylic acid or monoamine is preferred from the viewpoint of reactivity and stability of the blocked end, and monocarboxylic acid is more preferred from the viewpoint of ease of handling, etc., and acetic acid, propionic acid, butyric acid, valeric acid, caproic acid, caprylic acid, lauric acid, tridecylic acid, myristic acid, palmitic acid, stearic acid, and benzoic acid are preferred from the viewpoints of reactivity, stability of the blocked end, cost, etc.
[0023] (Semi-aromatic polyamide film) The semi-aromatic polyamide film of the present invention is a film made of the above-mentioned semi-aromatic polyamide resin, and has a heat shrinkage stress (HS 200,MD , H.S. 200,TD ) must be 0.2 to 2.0 MPa, and the heat shrinkage stress (HS 250,MD , H.S. 250,TD ) must be 0.5 to 3.0 MPa.
[0024] If the thermal shrinkage stress in the MD and TD at 200°C is not 0.2 MPa or more, it is difficult to impart sufficient shrinkage stress to the film part held by the holding member, and sagging occurs in the film part. The thermal shrinkage stress is preferably 0.3 MPa or more, and more preferably 0.5 MPa or more. On the other hand, if the heat shrinkage stress in the MD and TD at 200°C is not 2.0 MPa or less, the shrinkage stress is too large and wrinkles will occur in the film portion. The heat shrinkage stress is preferably 1.5 MPa or less, and more preferably 0.7 MPa or less.
[0025] Furthermore, if the thermal shrinkage stress in the MD and TD at 250°C is not 0.5 MPa or more, it is difficult to impart sufficient shrinkage stress to the film part held by the holding member, and sagging occurs in the film part. The thermal shrinkage stress is preferably 0.7 MPa or more, and more preferably 1.5 MPa or more. On the other hand, if the heat shrinkage stress in the MD and TD at 250°C is not 3.0 MPa or less, the shrinkage stress is too large and wrinkles will occur in the film portion. The heat shrinkage stress is preferably 2.5 MPa or less, and more preferably 2.0 MPa or less.
[0026] The semi-aromatic polyamide film of the present invention has a thermal shrinkage stress difference between MD and TD at 200°C and 250°C, which is the absolute value of |HS 200,MD -HS 200,TD | and |HS 250,MD -HS 250,TD It is preferable that each of | is 1.0 MPa or less. The absolute value of the difference in heat shrinkage stress is an evaluation of the in-plane uniformity of the heat shrinkage stress, and the smaller the value, the better. It is preferably 1.0 MPa or less, more preferably 0.7 MPa or less, and even more preferably 0.5 MPa or less.
[0027] In addition, in the semi-aromatic polyamide film of the present invention, ||HS 200,MD -HS 200,TD |-|HS 250,MD -HS 250,TD || is an evaluation of the temperature dependency of the in-plane uniformity, and is preferably 0.5 MPa or less, more preferably 0.3 MPa or less, and further preferably 0.1 MPa or less.
[0028] The thickness of the semi-aromatic polyamide film of the present invention is not particularly limited, but the thickness unevenness R is preferably 8% or less, more preferably 6% or less, and even more preferably 4% or less. If the thickness unevenness R of the semi-aromatic polyamide film exceeds 10%, it may cause sagging or wrinkles in the film during processing and cause poor quality of the final product. The thickness unevenness R is calculated by the following formula, where the thickness of the film obtained by stretching is measured every 10 mm in the film width direction using a thickness meter "MT12B" manufactured by HEIDENHAIN Corporation, and the maximum measured value is Lmax, the minimum value is Lmin, and the average value is La. R = ((Lmax-Lmin) / 2La) x 100
[0029] In order to further improve the various properties of the semi-aromatic polyamide film of the present invention, as necessary, additives such as lubricants, pigments such as titanium, colorants such as dyes, color inhibitors, heat stabilizers, hindered phenols, antioxidants such as phosphates and phosphites, weather resistance improvers such as benzotriazole-based compounds, bromine-based and phosphorus-based flame retardants, plasticizers, release agents, reinforcing agents such as talc, modifiers, antistatic agents, ultraviolet absorbers, anti-fogging agents, and various polymer resins may be contained within the range that does not sacrifice the various properties of the film.
[0030] The semi-aromatic polyamide film of the present invention preferably contains fine particles as an additive to improve the slipperiness. Examples of the fine particles include inorganic particles such as silica, alumina, titanium dioxide, calcium carbonate, kaolin, barium sulfate, etc., and organic particles such as acrylic resin particles, melamine resin particles, silicone resin particles, crosslinked polystyrene particles, etc. The average particle size of the fine particles can be selected within the range of 0.05 to 5.0 μm depending on the frictional properties, optical properties, and other properties required for the film.
[0031] Various methods can be used to incorporate additives into the film, including, for example, a method of adding additives during polymerization of the semi-aromatic polyamide, a masterbatch method in which additives are added directly to the semi-aromatic polyamide and melt-kneaded to prepare pellets, a method in which additives are added directly to the semi-aromatic polyamide during sheet formation and melt-kneaded in an extruder, and a method in which additives are added directly to an extruder during sheet formation and melt-kneaded.
[0032] The semi-aromatic polyamide film of the present invention may be subjected to a corona treatment, a plasma treatment, an acid treatment, a flame treatment, a coating treatment, or the like in order to improve the adhesiveness of the film surface. In addition, various coating agents may be applied to the surface of the semi-aromatic polyamide film in order to impart functions such as easy adhesion, antistatic properties, releasability, gas barrier properties, etc. The coating agent may be applied to the film after stretching or before stretching, or may be applied to the film immediately before stretching and then dried in a preheating section of the stretching machine to form a film.
[0033] The raw material for the semi-aromatic polyamide film of the present invention may be a mixture of virgin raw materials, or may be a mixture of scraps generated as off-standard films or edge trimmings during the production of a semi-aromatic polyamide stretched film, or may be prepared by adding virgin raw materials to the scrap mixture. These may be mixed by known methods such as a dry blending method using a known device, or a kneading method in which melt kneading is performed using a single-screw or twin-screw extruder.
[0034] (Method of manufacturing semi-aromatic polyamide film) Next, the method for producing the semi-aromatic polyamide film of the present invention will be described in detail. In producing the semi-aromatic polyamide film of the present invention, the semi-aromatic polyamide resin or a mixture thereof with additives is melt-extruded in an extruder, and the polymer melt is discharged in the form of a sheet from a flat die such as a T-die or an I-die. The sheet is then cooled by contacting it with the cooling surface of a moving cooling body such as a cooling roll or a steel belt to obtain an unstretched film.
[0035] The extrusion temperature is preferably equal to or higher than the melting point (Tm) of the semi-aromatic polyamide resin and equal to or lower than 370° C. If the extrusion temperature is lower than the melting point, the viscosity may increase and extrusion may become impossible, whereas if the extrusion temperature exceeds 370° C., the semi-aromatic polyamide may decompose.
[0036] The temperature of the moving cooling body is preferably 20 to 90° C., more preferably 30 to 70° C., and even more preferably 40 to 60° C. Polyamide usually has a high crystallization rate, and slow cooling causes crystal growth and makes stretching difficult, so it is common to rapidly cool it to near room temperature in order to simultaneously increase the cooling efficiency and suppress condensation of water droplets on the moving cooling body. If the temperature of the moving cooling body exceeds 90°C, it takes longer for the molten polymer to develop an appropriate hardness on the moving cooling body, making it difficult to remove from the moving cooling body. As a result, for example, if the moving cooling body is a roll, the film may break and wrap around the roll, or even if it does not break, the force of the film coming off the roll may cause pulsation. Also, crystals of various sizes may form in the unstretched film, causing uneven stretching or making stretching difficult. When the semi-aromatic polyamide resin of the present invention is quenched with a moving cooling body of less than 20°C, the part of the molten polymer that has not yet come into contact with the moving cooling body (cooling roll) hardens, and the hardened part may not adhere to the moving cooling body (cooling roll). As a result, the unstretched film has parts that adhere to the moving cooling body and parts that do not, making it impossible to operate stably. In addition, breakage or uneven stretching occurs in the subsequent stretching process. This is thought to be due to the fact that, in addition to the resin characteristic of a fast crystallization rate, the resin characteristic of a high glass transition temperature (Tg) and a high elastic modulus and hardness in the low temperature range prevent uniform adhesion with the moving cooling body, causing localized unevenness in the cooling rate.
[0037] In order to uniformly cool and solidify a polymer melt to obtain a sheet, methods for cooling and solidifying the polymer melt by bringing it into close contact with a moving cooling body include air knife casting, electrostatic application, and vacuum chamber methods.
[0038] The obtained unstretched film usually has a thickness of about 10 μm to 3 mm, and has excellent properties such as low water absorbency and chemical resistance even as it is. However, by biaxially stretching to a thickness of about 0.5 μm to 1.5 mm, the low water absorbency, chemical resistance, heat resistance, and mechanical strength are further improved.
[0039] Examples of the stretching method include flat-type sequential biaxial stretching, flat-type simultaneous biaxial stretching, tubular method, etc. Among them, the flat-type simultaneous biaxial stretching is most suitable since it can provide a film with good thickness accuracy and uniform physical properties in the width direction. Examples of the stretching device for the flat-type simultaneous biaxial stretching method include a screw-type tenter, a pantograph-type tenter, and a linear motor-driven clip-type tenter.
[0040] The stretching ratio is preferably in the range of 2.0 to 10 times, and more preferably 2.5 to 4.0 times, in both the machine direction (MD) and the transverse direction (TD) in order to provide the final semi-aromatic polyamide film with excellent heat resistance and mechanical strength.
[0041] The stretching speed is preferably such that both the MD and TD stretching strain rates exceed 400% / min, more preferably 800 to 12000% / min, and even more preferably 1200 to 6000% / min. If the strain rate is 400% / min or less, crystals may grow during stretching, causing the film to break. Conversely, if the strain rate is too fast, the unstretched film may be unable to keep up with the deformation and break.
[0042] It is preferable that the unstretched film is preheated before stretching. In order to obtain the semi-aromatic polyamide stretched film of the present invention, it is preferable that the preheating temperature Tp and the preheating time tp satisfy the relationship of the following formula (1), and Tp is (Tg-20) to (Tg+40)°C. Tp is preferably (Tg-15) to (Tg+35)°C. In addition, a practical range of tp is 1 to 60 seconds. 1×10 4 ×EXP(-0.06×Tp)≦tp≦2×10 7 ×EXP(-0.1×Tp) (1) If the preheating temperature Tp is less than (Tg-20)°C, the film is likely to break during stretching, the load on the stretching machine is large, and equipment troubles are likely to occur. If the preheating temperature exceeds (Tg+40)°C, uneven stretching and film breakage are likely to occur, and the load on the stretching machine may also be large. When the left side of the formula (1) above is not satisfied, the film is not preheated sufficiently, and the film is stretched while still hard. This can result in the film breaking or the stretching stress becoming too high, which can increase the load on the equipment and cause breakdowns. In addition, when the right side of the formula (1) above is not satisfied, the film is preheated excessively, and crystallization proceeds before stretching. Therefore, although it is desirable to achieve oriented crystallization by the stretching operation, crystallization proceeds partially before stretching, which tends to cause unevenness and breakage. The stretching temperature is preferably equal to or higher than Tg, and more preferably higher than Tg and equal to or lower than (Tg+30)° C. If the stretching temperature is lower than Tg, the film is likely to break and stable production may not be possible. Conversely, if the temperature exceeds (Tg+30)° C., uneven stretching may occur.
[0043] After the above-mentioned stretching, the film is preferably heat-set while still being held by the clips for stretching. The heat-set temperature is preferably 280°C to (Tm-25)°C. Furthermore, after the heat setting treatment, the film while still being held by the clips is preferably subjected to a relaxation treatment at a relaxation rate of 0.5 to 10.0% as necessary, and more preferably a relaxation rate of 0.5 to 5.0%. By appropriately performing the relaxation treatment, the film can obtain appropriate thermal stability, and by performing the relaxation treatment simultaneously in MD and TD, higher dimensional stability can be obtained. Although the detailed mechanism is unknown, the heat shrinkage stress of a film tends to increase when the stretching ratio is increased, and tends to decrease when the heat treatment temperature and relaxation rate are increased; the heat shrinkage stress of the film can be controlled by appropriately combining the respective processing conditions.
[0044] After the heat setting and relaxation treatments, the film is cooled and wound on a take-up roll to obtain a semi-aromatic polyamide film roll. The obtained semi-aromatic polyamide film roll can be slit to a desired width to be used again as a semi-aromatic polyamide film roll.
[0045] The semi-aromatic polyamide film of the present invention can be continuously produced as a film having a length of 100 m or more. Although the semi-aromatic polyamide film can be cut into sheets, it is preferable to make it into a film roll from the viewpoint of productivity when used for various applications.
[0046] (Application) The semi-aromatic polyamide film of the present invention can be used in a device including a film holder, and the semi-aromatic polyamide film held by the holder can be used in a heat-treated, shrunk state. Examples of the device include a tactile switch, a speaker, a voice transmitter, and a musical instrument such as a drum. EXAMPLES
[0047] The present invention will be specifically described below with reference to examples. <Evaluation method> The methods for evaluating various physical properties in the following Examples and Comparative Examples are as follows. Unless otherwise specified, all measurements were performed in an environment of a temperature of 23° C. and a humidity of 50%.
[0048] 1.Heat shrinkage stress measurement The thermal shrinkage stress was measured using Hitachi High-Tech Science TMA7100. After adjusting the temperature and humidity of the sample at 23°C and 50% RH, the sample was cut to a width of 5 mm and placed in the device so that the measurement length was 10 mm. The temperature was raised from 25°C to 250°C in a nitrogen atmosphere, and the thermal shrinkage force was measured. The cross-sectional area was calculated from the width and thickness of the sample before measurement, and the thermal shrinkage stress was calculated. The thermal shrinkage stress in the MD at 200°C was calculated using the HS 200,MD , TD thermal shrinkage stress is HS 200,TD , MD thermal shrinkage stress at 250℃ is HS 250,MD , MD thermal shrinkage stress is HS 250,TD It was decided.
[0049] 2. Observation of appearance after heat treatment A sample was cut into a square shape of 40 mm in the MD and 40 mm in the TD from a doughnut-shaped aluminum disk with an outer diameter of 54 mm and an inner diameter of 36 mm, and fixed in eight places (MD, TD, and four corners) using Nitto Denko polyimide tape (360UL), and heat-treated at 200°C for 5 minutes using AS ONE hot air dryer (DOV-600A), and the appearance was observed. For samples that had no problems with the appearance, they were returned to room temperature and then heat-treated at 250°C for another 5 minutes, and the appearance was checked.
[0050] <Method of producing semi-aromatic polyamide resin> 3289 parts by mass of terephthalic acid (TA), 2533 parts by mass of 1,9-nonanediamine (NMDA), 633 parts by mass of 2-methyl-1,8-octanediamine (MODA), 48.9 parts by mass of benzoic acid (BA), 6.5 parts by mass of sodium hypophosphite monohydrate (0.1% by mass relative to the total of the four polyamide raw materials), and 2200 parts by mass of distilled water were placed in a reaction vessel and substituted with nitrogen. The ratio of these was TA / BA / NMDA / MODA = 99 / 2 / 80 / 20 (molar ratio). After stirring at 100°C for 30 minutes, the internal temperature was raised to 210°C over 2 hours. At this time, the reaction vessel was pressurized at 2.12 MPa (22 kg / cm 2 The reaction was continued for 1 hour, after which the temperature was raised to 230°C and kept at 230°C for another 2 hours. The steam was gradually released and the pressure was reduced to 2.12MPa (22kg / cm 2 The reaction was carried out while maintaining the pressure at 0.98 MPa (10 kg / cm) for 30 minutes. 2 ), and reacted for another hour to obtain a prepolymer with an intrinsic viscosity of 0.30 dl / g. This was dried at a temperature of 100°C under reduced pressure for 12 hours, and then pulverized to a size of 2 mm or less. This was then solid-phase polymerized for 10 hours under conditions of a temperature of 230°C and a pressure of 13.3 Pa (0.1 mmHg) to obtain a white semi-aromatic polyamide resin with a melting point of 290°C and an intrinsic viscosity of 1.25 dl / g. This was fed to a twin-screw extruder (Japan Steel Works, Ltd., "TEX44C"), melt-kneaded and extruded under conditions of a cylinder temperature of 320°C, cooled, and cut to produce a pellet-shaped semi-aromatic polyamide resin.
[0051] Example 1 A resin modifier (Tafmer MH7020 manufactured by Mitsui Polymer Co., Ltd.) was added to the pellet-shaped semi-aromatic polyamide resin by the master batch method so as to be 5% by mass, and then the resin was melted by feeding it into a 65 mm single screw extruder with cylinder temperatures set to 290 ° C (front stage), 320 ° C (middle stage), and 320 ° C (rear stage), and extruded into a sheet from a T-die set to 320 ° C, and cooled by contacting with the cooling surface of a cooling roll to obtain an unstretched film with a thickness of 240 μm. The temperature of the moving cooling body was set to 20 to 50 ° C, and the unstretched film was rapidly cooled to obtain a substantially unoriented unstretched film. Next, while both ends of this unstretched film were held with clips, simultaneous biaxial stretching was performed using a Bruckner KAROIV batch-type stretching machine under the conditions of a stretching temperature of 120°C, a machine direction (MD) stretch ratio of 3.0 times, and a transverse direction (TD) stretch ratio of 3.0 times. After stretching, the film was heat-set by applying hot air at 280°C, and at the same time, a relaxation treatment was performed in MD and TD at a relaxation rate of 2.0%.
[0052] Examples 2 to 10, Comparative Examples 1 to 12 Semi-aromatic polyamide films were obtained in the same manner as in Example 1, except that the presence or absence of a resin modifier, the stretch ratio, the heat setting temperature, and the relaxation rate were changed as shown in Table 1.
[0053] Example 11 After obtaining an unstretched film in the same manner as in Example 1, the unstretched film was introduced into a tenter-type simultaneous biaxial stretching machine (manufactured by Hitachi, Ltd.) with an inlet width of 193 mm and an outlet width of 605 mm while holding both ends of the unstretched film with clips, and simultaneously biaxially stretched at a preheating section temperature of 130° C., a stretching section temperature of 130° C., an MD stretching strain rate of 2400% / min, a TD stretching strain rate of 2400% / min, an MD stretching ratio of 3.0 times, and a TD stretching ratio of 3.0 times. In the tenter, heat setting was performed at 280° C., and the TD of the film was subjected to a heat relaxation treatment with a relaxation rate of 2.5%, and then the film was uniformly cooled slowly, both ends of the film were released from the clips, and the edge portions were trimmed to obtain a film roll.
[0054] Comparative Examples 13 and 14 A film roll was obtained in the same manner as in Example 11, except that the presence or absence of a resin modifier, the heat setting temperature, and the relaxation rate were changed as shown in Table 1.
[0055] Comparative Example 15 The unstretched film obtained in Example 1 was measured and evaluated.
[0056] Table 1 shows the production conditions and evaluation results for the films of the examples and comparative examples.
[0057] [Table 1]
[0058] The films obtained in Examples 1 to 10 had heat shrinkage stress values in the suitable ranges at 200°C and 250°C, and therefore could be suitably used in devices including heat shrink processing methods, and there were no problems with the appearance after heat treatment.
[0059] On the other hand, the films of Comparative Examples 1, 2, 6, 11, and 12 had a low relaxation rate and therefore had high thermal shrinkage stress. The films of Comparative Examples 1 and 6 wrinkled when heat-treated at 250°C, and the films of Comparative Examples 2, 11, and 12 wrinkled after heat-treatment at 200°C and showed peeling in some areas. The films of Comparative Examples 3, 4, and 5 had a poor combination of heat treatment temperature and relaxation rate, and the relaxation rates were uneven, so the thermal shrinkage rates were unbalanced and outside the preferred range, and wrinkles and sagging occurred after heat treatment at 200°C. In the films of Comparative Examples 7 to 10, the heat treatment temperature was low relative to the stretching ratio, so that the heat shrinkage stress was high, and wrinkles were generated in the films after heat treatment at 200° C., and peeling was observed in some parts. The film of Comparative Example 13 was heat treated at a higher temperature than that of Example 11, and therefore had a lower heat shrinkage stress, and sagging occurred in the film after heat treatment at 200°C. The film of Comparative Example 14 was subjected to a lower heat treatment temperature than that of Example 11, and therefore the heat shrinkage stress was high, and wrinkles were generated in the film after heat treatment at 250°C. The unstretched film of Comparative Example 15 had a low heat shrinkage stress, and sagging occurred in the film after heat treatment at 200°C.
Claims
1. A film made of a semi-aromatic polyamide resin, Heat shrinkage stress (HS) at 200°C in the machine direction (MD) and cross direction (TD) 200,MD , H.S. 200,TD ) are 0.2 to 2.0 MPa, Heat shrinkage stress (HS) at 250°C in the machine direction (MD) and cross direction (TD) 250,MD , H.S. 250,TD ) are each 0.5 to 3.0 MPa.
2. | H.S. 200,MD -H.S. 200,TD | and | H.S. 250,MD -H.S. 250,TD The semi-aromatic polyamide film according to claim 1, characterized in that | is 1.0 MPa or less.
3. | | H.S. 200,MD -H.S. 200,TD |-|HS 250,MD -H.S. 250,TD The semi-aromatic polyamide film according to claim 1 or 2, characterized in that || is 0.5 MPa or less.
4. A device comprising the semi-aromatic polyamide film of claim 1 and a film holder.
5. 5. The device according to claim 4, wherein the semi-aromatic polyamide film held in the holding portion is heat-shrunk.
6. 6. The device according to claim 4 or 5, characterized in that the device is a tactile switch.
7. 6. A device according to claim 4 or 5, characterized in that the device is a voice transmitter.
Citation Information
Patent Citations
Voice-transmission device
JP2014176634A
Thermal adhesive tape for tactile switch
JP2020147696A
Semiaromatic polyamide film and method for producing same
WO2019031428A1
Cited By
Electron beam application device
US12437958B2